Progressive Law Perspective: Analysis of Restorative Justice in National Criminal Code - Pedju, Rizaldy Purnomo; Muhammad, Adamu Abubakar; Burhan, Putri Ajeng; Dzulqarnain, Andi (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2025)
Progressive law demands more open-mindedness to the possibility of alternative solutions in solving legal problems. In this case, the application of restorative justice is expected to have a positive impact on justice, not only in the formal legal context, but also in a broader social context. The purpose of this paper is to analyze the changes to criminal law in Law Number 1 of 2023 (later referred to as the National Criminal Law). How the application of restorative justice in the National Criminal Law is viewed from the perspective of progressive law. The method used is descriptive-normative, by collecting normative legal data, such as laws or regulations, to identify and understand its application in practice. The results show that Restorative justice offers a more humanist approach in resolving criminal cases, which focuses not only on punishment, but also on restoring the relationship between the perpetrator, the victim, and the community. Articles in the National Criminal Law indicate the existence of restorative justice in Article 54, Article 132 Paragraph 1 Letter g, Article 82, Articles 76, 77, and 80 (Reason for Termination of Prosecution), 132 Paragraph 1 Letters d and e. Restorative Justice in the National Criminal Law with a progressive legal approach provides opportunities for non-criminal settlements (diversion), recognition of victims, restorative justice, settlement with a substantive justice approach, alternative criminal sanctions. Through the application of restorative justice, the Indonesian criminal justice system has the potential to focus more on recovery and rehabilitation, reduce the burden on the courts, and support the social reintegration of offenders, which will create a more harmonious and just society. ___ References Books with an author: Dahl, R. A. (1988). On Democracy, London: Yale University. Nakamura, R. T., & Smallwood, F. (1980). The Politics of Policy Implementation, New York: St. Martin’s Press. Varma, S. P. (1975). Teori Politik Modern, Jakarta: Raja Grafindo Persada. Journal articles: Abdurrachman, H., Hamzani, A. I., Sudewo, F. A., Aravik, H., & Khasanah, N. (2021). Application of Ultimum Remedium Principles in Progressive Law Perspective. International Journal of Criminology and Sociology, 10, 1012-1022. https://doi.org/10.6000/1929-4409.2021.10.119 Afifah, H. (2024). Keadilan Restoratif dalam Dinamika Pembaruan Hukum Pidana Indonesia. Jurnal Syntax Admiration, 5(8), 3007-3015. https://doi.org/10.46799/jsa.v5i8.1392 Agusta, D., Madjid, A., & Aprilianda, N. (2025). Reforming Indonesian Criminal Law: Integrating Supervision, Punishment, and Rehabilitation for Restorative Justice. International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 7(1), 54-68. https://doi.org/10.47006/ijierm.v7i1.434 Agustina, V., Tisnanta, H. S., & Muhtadi, M. (2024). Restorative Justice as an Effort to Fulfill the Constitutional Rights of Citizens: Restorative Justice sebagai Upaya Pemenuhan Hak Konstitusional Warga Negara. Jurnal Konstitusi, 21(2), 244-257. https://doi.org/10.31078/jk2125 Ahyad, R. The Essence of Discontinuing Prosecution by the Prosecutor's Office to Achieve Restorative Justice. Ratio Legis Journal, 3(1), 1083-1091. http://dx.doi.org/10.30659/rlj.3.1.821-830 Bassiouni, M. C. (2006). International recognition of victims' rights. Human Rights Law Review, 6(2), 203-279. https://doi.org/10.1093/hrlr/ngl009 Braithwaite, J. (1996). Restorative justice and a better future. The Dalhousie Review, 76(1), 9-32. http://hdl.handle.net/10222/63177 Carlsmith, K. M., & Darley, J. M. (2008). Psychological aspects of retributive justice. Advances in experimental social psychology, 40, 193-236. https://doi.org/10.1016/S0065-2601(07)00004-4 Casper, G., & Posner, R. A. (1974). A Study of the Supreme Court's Caseload. The Journal of Legal Studies, 3(2), 339-375. https://www.jstor.org/stable/724018 Crocker, D. (2016). Balancing justice goals: Restorative justice practitioners’ views. Contemporary justice review, 19(4), 462-478. https://doi.org/10.1080/10282580.2016.1226815 Daly, K. (2016). What is restorative justice? Fresh answers to a vexed question. Victims & offenders, 11(1), 9-29. https://doi.org/10.1080/15564886.2015.1107797 Deneulin, S., & Townsend, N. (2007). Public goods, global public goods and the common good. International journal of social economics, 34(1/2), 19-36. https://doi.org/10.1108/03068290710723345 Fatmawati, E. (2021). Strategies to grow a proud attitude towards Indonesian cultural diversity. Linguistics and Culture Review, 810-820. https://doi.org/10.21744/lingcure.v5nS1.1465